Survey and molecular and pathological characterization of selected emerging infectious agents in aquatic mammals of Brazil - Benvenuto, Arícia Duarte (2023)
Aquatic ecosystems are fundamental resources for humanity, but increasingly threatened by the consequences of such interaction. Aquatic mammals are considered bioindicators of environmental health, serving as sentinels to evaluate anthropogenic and environmental impacts, and the emergence of infectious agents. Some of the known viral and bacterial etiologic agents affecting marine mammals (e.g., morbillivirus, Influenza virus) have been associated with high morbidity and mortality, and thus have been investigated more thoroughly. On the other hand, other agents have only been studied in punctual reports and remain poorly understood, including bacteria of Mycoplasma genus, and viruses within the Polyomaviridae family and Orthoflavivirus genus. Therefore, the main goal of this study was to investigate, identify and characterize, through molecular and pathological methods, the agents and infections (when present) caused by these selected emerging infectious agents (i.e.,hemotropic mycoplasma, Polyomaviridae and Orthoflavivirus) in samples from wild aquatic mammals of Brazil. All samples were provided by the Brazilian National Stranding Network between 2002 and 2022, and from scientific live captures in the Amazon biome in 2015, 2016, 2017 and 2020. Mycoplasma presence was evaluated in blood samples of aquatic mammals from the Amazon and marine biomes, with a total of 180 cetaceans, 49 sirenians and 18 pinnipeds tested. Regarding viral agents, we tested tissue and serum samples collected only from cetaceans, comprising 151 specimens for Orthoflavivirus and 119 for Polyomaviridae, accross 19 different cetacean species. Hemotropic mycoplasmas (hemoplasmas) were found in 50 cetaceans and in three pinnipeds; however, they were not detected in any of the tested sirenians. Among cetaceans, we observed a higher occurrence rate in riverine dolphins (32/50,64%) in comparison with marine species (18/130, 13.8%), with riverine dolphins presenting a genetic structure based on collection site and host species. Our findings indicate that although at least two species of hemoplasma are circulating in cetaceans, the majority of the retrieved sequences were very similar, suggesting a common ancestry. Additionally, we detected a systemic non-hemotropic mycoplasma in two Franciscana dolphins (Pontoporia blainvilei) presenting histologic lesions compatible with mycoplasmosis. In pinnipeds, the retrieved hemoplasma sequences were very similar with those previously reported, indicating low bacterial mutation rate. Polyomavirus was detected in two juvenile female (2/119; 1.7%) Guiana dolphins (Sotalia guianensis) co-infected with morbillivirus that stranded in 2018. The anatomopathological findings and retrieved sequences were very similar to those of a previous infection detected in a short-beaked common dolphin (Delphinus delphis) from the Northern Hemisphere. Phylogenetic analysis suggest that the detected polyomavirus is a potential novel species specific of Guiana dolphins with tropism for the respiratory system. We did not detect flavivirus in any of the 586 tested samples. Herein we report the first worldwide detection of hemoplasma in cetaceans and the second in pinnipeds, and the first detection of non-hemotropic mycoplasma and polyomavirus in cetaceans of the Southern Hemisphere, broadening the knowledge of viral and bacterial agents affecting and circulating in aquatic mammals.